Basic Concepts of the Teaching Professionalism in Elementary Education Institutions - Raden Fadli Daulay; Riki Irawan; Siti Nurhalizah; Wildan Murtadho; Amiruddin Siahaan; Amiruddin Amiruddin (Universitas Pahlawan Tuanku Tambusai, 2023)
The teaching profession is considered important as a basic milestone for the progress of a nation, because developed nations have quality education. The quality of education is very dependent on the competence possessed by educators, especially teachers at the elementary age level of SD/MI as the initial level of formal education for the nation's children. This study aims to describe the basic concepts of the teaching profession in primary education institutions SD/MI. This type of research includes a qualitative approach with library research methods. Sources of data and materials for analysis of the study use scientific literature relevant to the topic of discussion, including books, articles, seminar proceedings, and final assignments (thesis, dissertation). The data is obtained from credible sources such as Google Scholar and Sinta. The results of this study concluded that the teaching profession has a code of ethics that students should emulate, which includes teaching skills, mastery of areas of expertise, behavior/personality and teacher communication skills. Because, in it there is an organizational platform, the role of rights and obligations of teachers to guide directing students and evaluating good and specifically directed teaching and learning processes.